Effect of Bandotan (Ageratum conyzoidez L) Leaf Extract on Total Blood Cholesterol Levels of Broiler - Egi Supriyadi; Roslizawaty Roslizawaty; Zuhrawati Zuhrawati (Universitas Syiah Kuala, 2014)
This study aimed to determine the effect of bandotan (Ageratum conyzoides L) leaf extract on total blood cholesterol level of broiler. This study used 15 broiler aged of 25 days. This study was an experimental study using completely randomized design (CRD) unidirectional pattern with 3 treatment groups and 5replications each. Group 0 (P0) was not given bandotan leaf extract, group 1 (P1) was given 3 ml bandotan leaf extract, and group 2 (P 2) was given 5 ml bandotan leaf extract. The administration of Bandotan leaf extract was carried out once a day for 5 consecutive days. On day 6 after treatment, the blood was collected then examined for total blood cholesterol level by precipitation method. Data was analyzed using analysis of variance. The result showed that the average of total cholesterol level on group P0, P1, and P2 was 134.20+10.50, 125.15+8.20, and 113.34+7.50 mg/dl, respectively. In conclusion, bandotan leaf extract decrease blood cholesterol levels of broiler.Key words: broiler, bandotan leaf extract, total cholesterol level